Time-resolved spectroscopic investigation of charge trapping in carbon nitrides photocatalysts for hydrogen generation - Godin,RP; Wang,Y; Zwijnenburg,MA; Tang,J; Durrant,J (Journal of the American Chemical Society, 2017)
Carbon nitride (g-C3N4) as a benchmark polymer photocatalyst is attracting significant research interest because of its visible light photocatalytic performance combined with good stability and facile synthesis. However, little is known about the fundamental photophysical processes of g-C3N4, which are key to explain and promote photoactivity. Using time-resolved absorption and photoluminescence spectroscopies, we have investigated the photophysics of a series of carbon nitrides on time scales ranging from femtoseconds to seconds. Free charge carriers form within a 200 fs excitation pulse, trap on the picosecond time scale with trap states in a range of energies, and then recombine with power law decays that are indicative of charge trapping–detrapping processes. Delayed photoluminescence is assigned to thermal excitation of trapped carriers back up to the conduction/valence bands. We develop a simple, quantitative model for the charge carrier dynamics in these photocatalysts, which includes carrier relaxation into an exponential tail of trap states extending up to 1.5 eV into the bandgap. This trapping reduces the efficiency of surface photocatalytic reactions. Deep trapped electrons observed on micro- to millisecond time scales are unable to reduce electron acceptors on the surface or in solution. Within a series of g-C3N4, the yield of these unreactive trapped electrons correlates inversely with H2 evolution rates. We conclude by arguing that the photophysics of these carbon nitride materials show closer parallels with inorganic semiconductors than conjugated polymers, and that the key challenge to optimize photocatalytic activity of these materials is to prevent electron trapping into deep, and photocatalytically inactive, electron trap states.